Mental Health Development of Orphans and Dhu’afa: A Qur’anic-Based Approach in Muhammadiyah and NU Child Welfare Institutions - Saadi, Saadi; Mubasirun, Mubasirun; Othman, Siti Suriani (Journal of Education and Religious Studies, 2025)
Mental health has become a major concern that we need to address. Many verses of the Qur’an and hadith could serve as a source of inspiration for theoretical and practical development about the concepts of mental health. The Muhammadiyah and Darul Hadhanah NU Child Welfare Institution (LKSA) is an official institution that organizes care services for children with a range of social, religious, financial, and educational issues. The focus of this research is to identify factors that lead to mental health disorders as well as the strategies to prevent and treat them. This research is a field study, so the qualitative method serves as the basis of the research with a post-positivist philosophical approach. Researchers analyze empirical data as comprehensive information from the subjects. Content analysis is used to examine written sources related to the implementation of the understanding of nafsiyah verses in mental health development. The results of the study, shows that negative behaviors are the factors caused mental health disorder among the children. The provision of various services includes fulfilling physical needs (food), health, clothes, shelter, spiritual needs, psychological counseling, education, skills, social needs, recreation, and cultural creation. The Muhammadiyah and Darul Hadhanah NU Child Welfare Institution (LKSA) implement the understanding of nafsiyah verses by strengthening faith, instilling gratitude, patience, love for each other, and various physical needs.